G24 Capillary Malformations – Arteriovenous Malformations/Arteriovenous Fistula Syndrome (CM-AVM Syndrome): An Under Recognised Clinical Entity?. (4th June 2013) - Thanopoulou, I; Bhate, S; Burrows, N; Berg, J; Glover, M
Abstract : Background: Hereditary Hemorrhagic telangiectasia (HHT) tends to be the first condition to be considered in the differential diagnosis of patients presenting with high flow vascular malformations in combination with cutaneous vascular lesions. However, particularly in the paediatric population, capillary malformation-arteriovenous malformation syndrome (CM-AVM) due to RASA-1 mutation 1 is more likely. Aims: To present the clinical features of three patients with CM-AVM syndrome, promote knowledge of this condition and aid prompt diagnosis. Methods: Clinical examination, detailed family history, imaging (ultrasound, MRI, angiography) and genetic testing. Results: Patient 1 was born with a large vascular mass affecting the right side of the face and multiple cutaneous capillary malformations. Patient 2 had a spinal AV fistula and two vascular stains. Patient 3 presented with an intracranial haemorrhage secondary to a parietal AVM and was noted to have several cutaneous vascular lesions. Patients 2 and 3 were referred to the dermatology team as suspected HHT. The cutaneous vascular lesions present in all three patients were consistent with capillary malformations (in keeping with a diagnosis of CM-AVM) and were not typical of telangiectases. Conclusion: In patients with high flow CNS vascular lesions, it is crucial to establish the precise nature of cutaneous vascular lesions in order to request appropriate genetic testing and screening of relatives. Reference: Laurence M Boon, Nicole Revencu, Miikka Vikkula, Université catholique de Louvain, Brussels, Belgium.